Modern Web Development with Go: Build Real-World, Fast, Efficient and Scalable Web Server Apps Using Go Programming Language - Stojanović, Dusan (Orange Education PVT Ltd, 2023)
In this book, we are going to learn how to design, develop and deploy Web Server Applications using the Go programming language. In recent years, Go has become the industrial standard for these kinds of applications; so by learning this, a lot of good opportunities can be opened in the market. All subjects will be covered through various practical examples. This book will cover the state-of-the-art technology for the development of Web Applications and follow all industrial standards. At the beginning we will do the preparation for development. Here, we will learn the basics of the Go programming language, the basics of Web Servers, how to set up a project with Go, and how to design software solutions. Later, we will concentrate more on development. We will learn how to develop the application designed in the previous chapters, how to use different types of databases, how to test our application, and how to make it secure. At the end of the book, we will show how to deploy the application and monitor it after deployment. After reading this book, the readers can independently develop Web Server Applications or include themselves in already-started projects.